Does Small-Scale Organic Farming Contribute to the Local Environment—A Case Study in Suburban Shanghai, China - Hietala Reija; Liu Pingyang; Qi Shengxin (MDPI, 2022)
Small-scale organic farming is developing rapidly in China, especially in suburbs of megacities, and enriches the connotation of urban agriculture. Much attention has been paid to the socio-economic aspects of small-scale organic farming and takes for granted that it contributes to the local environment and the sustainable agriculture while little has been explored regarding its actual environmental contributions and associated influencing factors, especially in those rapid developing suburb areas. Based on the case study of three small-scale organic farms in the suburbs of Shanghai, we examined uncertificated organic farming practices, focusing on the farm diversity, fertilization and pest control without chemical inputs, and the restoration of biosystems. Potential of environmental contributions were evaluated from the production perspective of input reductions. It was found that such uncertificated small-scale organic farming does contribute to the local water environment, helping improve soil quality, and gradual recovery of farm biodiversity. However, all the environmental benefits are fragile and highly dependent on the profit availability and professional knowledge of the farm as well as the availability of policy supports.